Curriculum Integration and Implementation in Madrasah Tsanawiyah Fadllillah Tambak Sumur Waru Sidoarjo - Nugraha, Agus; Ihsani, A. Fikri Amiruddin; Pradana, Hengki hendra; Hariri, Muh. Mirwan (BRILIANT: Jurnal Riset dan Konseptual, 2022)
The purpose of this research was to determine the integration of the K13 curriculum and the islamic boarding school curriculum and its implementation in Madrasah Tsanawiyah Tambak Sumur. This research uses qualitative research methods with observation data collection techniques, interviews, and documentation. While the data analysis technique used is descriptive data analysis techniques, namely written and unwritten data from the community and observable behavior. So that in this case, the author seeks to thoroughly describe the actual situation. Based on the research conducted, it was found that the integrated curriculum at Madrasah Tsanawiyah Fadllillah was a curriculum development that eliminated the boundaries between the K13 curriculum subjects and the islamic boarding school curriculum subjects (TMI). This curriculum development can be interpreted as an effort to combine two different curricula in one educational institution. In order to achieve the goals of educational institutions, in addition to students mastering abilities in the K13 curriculum subjects, they can also master skills in the islamic boarding school curriculum subjects (TMI). Therefore, to improve the quality for the better, researchers suggest that always make every effort to improve facilities and infrastructure to support the learning process. So that it can improve quality and achieve the expected learning objectives.